2015
DOI: 10.1103/physrevlett.115.060402
|View full text |Cite
|
Sign up to set email alerts
|

Time-Delayed Quantum Feedback Control

Abstract: A theory of time-delayed coherent quantum feedback is developed. More specifically, we consider a quantum system coupled to a bosonic reservoir creating a unidirectional feedback loop. It is shown that the dynamics can be mapped onto a fictitious series of cascaded quantum systems, where the system is driven by past versions of itself. The derivation of this model relies on a tensor network representation of the system-reservoir time-propagator. For concreteness, this general theory is applied to a driven two-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
186
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(188 citation statements)
references
References 55 publications
2
186
0
Order By: Relevance
“…One can show that this is equivalent to allowing S to interact with each discrete input mode twice (the time interval between the two interactions representing the delay time), a dynamics that was tackled in Ref. [16] through a nice diagrammatic method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One can show that this is equivalent to allowing S to interact with each discrete input mode twice (the time interval between the two interactions representing the delay time), a dynamics that was tackled in Ref. [16] through a nice diagrammatic method.…”
Section: Discussionmentioning
confidence: 99%
“…The last property alongside their simple and intrinsically discrete nature make CMs advantageous case studies to investigate major open problems in quantum non-Markovianity once the basic model outlined above is modi ed so as to introduce a memory mechanism. Among the ways to endow a CM with memory are: adding ancillaancilla collisions [4][5][6][7][8][9][10], embedding S into a larger system [11][12][13][14][15], allowing S to collide with each ancilla more than once [16,17], assuming a correlated initial bath state instead of a product one [18][19][20][21][22][23][24][25] or initial system-bath correlations [26][27][28]. Typical tasks that can be accomplished through NM CMs constructed in one of these ways are: deriving well-de ned (i.e., unconditionally completely positive) NM MEs [4,5,[37][38][39], gaining quantitative information about the role of system-bath and/or intra-bath correlations in making a dynamics NM [6,10,[19][20][21][22], simulating highly NM dynamics or indivisible channels [7,18,24].…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem methods have been proposed employing the Liouville space [26], Matrix product state (MPS) evolution [27], and the Heisenberg picture [21].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, (i) in particular can suggest schemes to perform experimental simulations of non-Markovian dynamics [17] or provide valuable theoretical tools in the analysis of very large Hilbert space problems [18] and time-delayed quantum feedback [19]. Concerning (ii), in particular, in 2013 two of us [12] showed that one can use a collision model to work out a non-Markovian master equation that is both capable to interpolate between a Markovian and a strongly non-Markovian regime and, additionally, is ensured to be completely positive and trace preserving, namely two requirements that are in general hard to meet at the same time.…”
Section: Introductionmentioning
confidence: 99%